ANALISIS PEMASARAN JAGUNG DI DESA PANGKUSA KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA (Analysis of Corn Marketing in Pangkusa Village, Sangkub District, North Bolaang Mongondow Regency) - Aditama, Iksan; Ngangi, Charles R.; Mandei, Juliana R. (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to determine the corn marketing channesl and their efficiency in Pangkusa Village. This research was carried out from June to August 2021. The data collected in this study were primary data and secondary data. Primary data were obtained from farmers and traders using questionnaires. Secondary data were obtained from the Pangkusa Village Office, and relevant sources on the internet. A total of 45 farmers who were members of the corn farmer group were selected randomly (simple random sampling) as respondents. Sampling of corn traders as many as 6 people was carried out using the Snowball Sampling method. The results showed that there were four patterns of marketing channels for corn in Pangkusa Village, namely: (I) Farmer–Factory, (II) Farmer–Village Collector–Factory, (III) Farmer–Subdistrict Collector–Factory, (IV) Farmer–Village Collector– District-Factory Collector. The most efficient marketing channel in marketing corn seen from Margin and Farmers share, was marketing channel I, because farmers in channel I sold their production directly to the factory. Based on the margin and Farmers share, channel IV pattern was not efficient. The profit-to-cost ratio in each marketing agency was not efficient because the corn marketing agency did not provide evenly distributed profits.